CD68 as a multi-omic prognostic biomarker in digestive system cancers: correlations with tumor-infiltrating immune cells and immune checkpoints - Hui Li; Hui Zhang; Rujiang Dai; Dian Zheng; Jianghai Zhao; Hong Jing; Xuhui Ma; Lin Zhang; Weihong Sun; Zhimin Suo (Frontiers in Immunology)
Background and objectiveCD68 plays a crucial role in promoting phagocytosis. However, its expression level, prognostic value and the correlations with tumor-infiltrating immune cells (TIICs) or common tumor immune checkpoints (TICs) in human digestive system cancers (DSC) remain poorly understood. This study aims to investigate the expression levels, prognostic significance, and clinical implications of CD68, as well as its correlations with six TIICs and four common TICs in DSC.Materials and methodsWe analyzed CD68 mRNA and protein expression using online databases and immunohistochemistry (IHC) on tissue microarray (TMA) sections, comparing DSC tumor tissues with adjacent normal tissues. Overall survival (OS) was calculated to evaluate the prognostic value of CD68 in DSC. Additionally, correlations between CD68 expression and six TIICs (B cells, CD4+ T cells, CD8+ T cells, macrophages, NK cells, and cancer-associated fibroblasts) or four common TICs (PDCD1, CTLA4, IDO1, and CD40) were assessed using the Tumor Immune Estimation Resource (TIMER).ResultsCD68 mRNA expression was significantly higher in esophageal carcinoma (ESCA) and stomach adenocarcinoma (STAD) tissues compared to adjacent normal tissues, but lower in colon adenocarcinoma (COAD), liver hepatocellular carcinoma (LIHC), and pancreas invasive ductal carcinoma (PAAD). Protein expression of CD68 was significantly higher in COAD than in adjacent normal tissues, but lower in ESCA, LIHC, PAAD, and STAD. CD68 protein expression served as a prognostic marker in COAD and STAD. Furthermore, CD68 expression showed strong positive correlations with the six TIICs and significant positive correlations with the four TICs in DSC.ConclusionCD68 may serve as an essential prognostic biomarker in COAD and STAD and could be a promising candidate for diagnostic, prognostic, and therapeutic targeting in human DSC.